Utilization of Zakah Application as Zakah Management Innovation to Increase Zakah Potential - Tsauri, Shafwan; Ghufron, Moh. Idil (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2021)
This study wants to reveal how the BAZNAS zak?h application makes it easier for Muzakki to pay zak?h and the extent to which the effectiveness makes Muzakki fulfill their zak?h obligations. By using a qualitative approach, this research data comes from primary and secondary data. Researchers obtained primary data by conducting interviews with related parties such as the District BAZNAS and related parties. Meanwhile, secondary data is obtained by researchers from various literatures such as books, research journals, final academic assignments, and others related to this research, which can complement existing problems. The results of this study revealed that in 2017, the zak?h received by BAZNAS (Institutions that manage zak?h nationally) was IDR 6,224,371,269,471. After the payment of zak?h through this online zak?h application, the receipt of zak?h received by BAZNAS reached Rp 8,117,597,683,267, indicating that this application zak?h has become a tangible medium in increasing awareness of Muzakki for doing a zak?h. Keywords: Zak?h Online; Zak?h Application; Optimization of Zak?h Payments Abstrak: Penelitian ini ingin mengungkap bagaimana aplikasi zakat BAZNAS dalam memudahkan Muzakki membayar zakat dan sejauh mana efektifitas aplikasi ini menyadarkan para Muzakki menunaikan kewajiban zakatnya. Dengan menggunakan pendekatan kualitatif, data penelitian ini bersumber dari data primer dan sekunder. Data primer didapat oleh peneliti dengan melakukan wawancara pada pihak terkait seperti BAZNAS Kabupaten dan pihak-pihak terkait. Sedangkan data sekunder didapat dari berbagai literatur seperti buku, jurnal – jurnal penelitian, tugas akhir akademik dan lainnya yang berhubungan dengan penelitian ini yang dapat digunakan dalam melengkapi permasalahan yang ada. Hasil dari penelitian ini mengungkapkan bahwa sebelum ada aplikasi pembayaran akat online pada tahun 2017, zakat yang diterima oleh BAZNAS adalah sebesar Rp 6,224,371,269,471. Setelah diadakannya pembayaran zakat melalui aplikasi zakat online, penerimaan zakat yang diterima oleh BAZNAS mencapai Rp 8,117,597,683,267. Hal demikian mengindikasikan bahwa aplikasi zakat ini telah menjadi media kongkrit dalam meningkatkan kesadaran berzakat para Muzakki. Kata Kunci: Zakat Online; Aplikasi Zakat; Optimalisasi Pembayaran Zakat